7
$\begingroup$

It is very easy to show that the series $$\frac{1-1/2}{1\times2} - \frac{1-1/2+1/3}{2\times3} + \frac{1-1/2+1/3-1/4}{3\times4} - ...$$ i.e. $$\sum_{n=1}^{\infty} \frac{(-1)^{n+1}}{n(n+1)}[1-\frac{1}{2} + \frac{1}{3} - ...+ \frac {(-1)^{n}}{n+1}]$$ is convergent. Can one find its exact value? Or is it unreasonable to hope for such a thing? Thank you for your answers.

$\endgroup$
1
  • $\begingroup$ The first thing that came to mind is that you might need Cesaro summability or something (cf. exercise 12-37 in Apostol, Mathematical Analysis), but I'm not sure that gets you where you where you want to go. It seems reasonable that this might be possible. Have you tried Hardy's Divergent Series? There may be a simple answer (one way or the other), but I'm not seeing it. $\endgroup$ Sep 14, 2011 at 17:24

2 Answers 2

15
$\begingroup$

The interior sum is equal to $\int_0^1\frac{1-(-x)^{n+1}}{1+x}dx$ and $$ \sum _{n=1}^{\infty } \frac{(-1)^{n+1} \left(1-(-x)^{n+1}\right)}{n (n+1) (x+1)}= \frac{(x-1) \log (1-x)-x+\log (4)-1}{1+x}. $$ So the answer is eqaul to $$ \int_0^1 \frac{(x-1) \log (1-x)-x+\log (4)-1}{1+x}dx=\frac{\pi ^2}{6}+\log ^2(2)-2. $$

$\endgroup$
1
  • $\begingroup$ What do you mean by interior sum? $\endgroup$ Sep 4, 2012 at 10:24
12
$\begingroup$

Since

$$\frac1{n(n+1)}=\frac1n-\frac1{n+1},$$

we have

$$\begin{aligned} \sum_{n=1}^N\sum_{k=1}^{n+1}\frac{(-1)^{n+k}}{kn(n+1)} &=\sum_{n=1}^N\sum_{k=1}^{n+1}\frac{(-1)^{n+k}}{kn}+\sum_{n=2}^{N+1}\sum_{k=1}^n\frac{(-1)^{n+k}}{kn}\\\\ &=2\sum_{n=1}^N\sum_{k=1}^n\frac{(-1)^{n+k}}{kn}-\sum_{n=1}^N\frac1{n(n+1)}-1+\sum_{k=1}^{N+1}\frac{(-1)^{N+1+k}}{k(N+1)}\\\\ &=\sum_{n,k=1}^N\frac{(-1)^{n+k}}{kn}+\sum_{n=1}^N\frac1{n^2}-2+\frac1{N+1}+\frac{(-1)^{N+1}}{N+1}\sum_{k=1}^{N+1}\frac{(-1)^k}k\\\\ &=\left(\sum_{n=1}^N\frac{(-1)^{n}}n\right)^2+\sum_{n=1}^N\frac1{n^2}-2+\frac1{N+1}+\frac{(-1)^{N+1}}{N+1}\sum_{k=1}^{N+1}\frac{(-1)^k}k. \end{aligned}$$

As $\sum_{n=1}^\infty\frac{(-1)^n}n=-\log2$ and $\sum_{n=1}^\infty\frac1{n^2}=\frac{\pi^2}6$, this implies

$$\sum_{n=1}^\infty\frac{(-1)^{n+1}}{n(n+1)}\sum_{k=1}^{n+1}\frac{(-1)^{k+1}}k=(\log2)^2+\frac{\pi^2}6-2.$$

There may be a numerical error somewhere, but in principle the method should work.

$\endgroup$
2
  • 1
    $\begingroup$ This can't be right as stated because it's negative. But your method must work because I get $(\log 2)^2 + \pi^2/6 - 2$ by a different approach. $\endgroup$ Sep 14, 2011 at 18:34
  • 1
    $\begingroup$ ...which I see that Andrew just posted. $\endgroup$ Sep 14, 2011 at 18:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.